AN EXPLORATION OF STUDENTS’ ANXIETY IN ONLINE FOREIGN LANGUAGE LEARNING - Anggraini, Hesti Wahyuni; Hayati, Rita; Sari, Armilia (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2022)
Technology use creates new insights to explore thoroughly online foreign language learning. This study aims to examine students’ anxiety in online classes under four research objectives. They are (1) to uncover students’ anxiety levels in online foreign language learning; (2) to investigate the effects of anxiety levels in online learning on students’ English achievement; (3) to reveal factors affecting student’s anxiety; and (4) to investigate students’ strategies to handle their anxiety in online learning. Questionnaires were distributed to 72 students from a public university in South Sumatra, Indonesia. In addition, a semi-structured interview was also administered. The data was described quantitatively and qualitatively. The findings show that most students felt a medium level of anxiety in online learning. The students did not significantly experience unusual levels of anxiety as they were accustomed to technology tools and found no problems with that. A negative correlation between students’ anxiety scale on online learning and their academic achievement was identified. Indirect feedback, minimum teacher-and-student presence, and the absence of eye contact could be the main factors of online learning failure. Peer intimidation and fear of speaking English might also be the sources of students’ anxiety in online learning. Students also stated that there are no specific ways to handle anxiety since it is viewed as an unstable foreign language learning factor, which can be changed based on the learning context. At last, it is expected that the result of the study can raise students’ awareness of how online class can reduce their anxiety.